Tai chi impact on equilibrium, fatigue and psychoemotional state of persons with multiple sclerosis - Tubytė, Ilona; Andrejeva, Julija; Razbadauskas, Artūras; Žuravliova, Tatjana; Volkova, Olesya (Slauga. Mokslas ir praktika, 2020)
The aim of this study was to determine the effects of Tai Chi on balance, fatigue and psichoemotional state in persons with multiple sclerosis.Multiple sclerosis (MS) is a chronic progressive neurologic disease of the central nervous system that most common affects people between the age of 20-40 years old. The symptoms associated with MC cause mobility limitations, such as balance and gait impairment and in the later stages of disease getting worst. Not only motor impairment ocur but and fatigue, emotional changes are also frequently present in MS. This represents an importance to find a comprehensive exersice maintaine physical fitness to keep maximal independency and quality of life. The existing evidence supports the effectiveness of 6 months of mind-body therapy Tai Chi for persons with multiple sclerosis (MS) in various domains including, balance, coordination and depression. However, we are not aware of any previous studies of the effects of 2 months of Tai Chi on balance, fatigue and psicho emotional state in persons with MS.Material and methods. 11 participants with relapsing-remitting MS participated in this study. The intervention consisted of a 60-min Tai Chi exercise program twice a week, for 8 weeks. Static and dynamic balance, walking speed, fatigue psycho emotional state were evaluated before and after the 8 weeks. Statistical analyses were performed with the use of SPSS software, version 21 (IBM), the result reliable when p 0,05).
Keywords: fatigue; walking; depression